PENGARUH HARGA TERHADAP KEPUASAN PELANGGAN PRODUK KELOM SHENY DI KOTA TASIKMALAYA - Arif Arif; Depy Muhamad Pauzy (Jurnal Bina Manajemen, 2022)
This study aims to examine the effect of price on customer satisfaction of Kelom Sheny products in Tasikmalaya City. In this study using a quantitative approach with a simple random sampling technique with 100 respondents. The results of the validity and reliability test showed that Cronbach's Alpha coefficient was more than 0.60. Then, linear regression analysis with t test value is 0.874. The value of r square is 0.008 or the effect of price on customer satisfaction is only 0.8%, it shows that 99.2% of customer satisfaction is influenced by other variables. Based on the results of these data, the effect of price on customer satisfaction has no significant effect